The Impact of Foreign Investment on Economic Growth in Regencies/ Municipalities of West Java Province - Akhmalul Akbar, Muhammad Ilham; Al Muizzuddin Fazaalloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The West Java Province region is an area that has the highest amount of foreign investment compared to other provinces on the island of Java. Foreign Direct Investment (FDI) is one of the most important factors aimed at boosting the economy of a country/region. Therefore, this research aims to analyze the impact of Foreign Direct Investment (FDI) on economic growth in West Java Province. By using secondary data in the form of data on the amount of foreign investment, government expenditure, labor and gross regional domestic product (GRDP) during the period 2010-2023 in West Java Province. Data analysis and hypothesis testing were carried out using Dynamic Panel Data Analysis (GMM) using the Stata-17 application. The results of this research partially show that the Foreign Investment and Government Expenditure variables have a positive and significant effect on Economic Growth, while the Labor variable has a significant negative effect on Economic Growth.